Profil Asam Lemak Maggot BSF Yang Dibudidaya Menggunakan Media Pakan Sumber Hewani dan Nabati - Dwi Kusuma Purnamasari; K.G. Wiryawan; Erwan Erwan; V. Maslami; J. Klana; D. Saputra (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2025)
The study aimed to obtain data on the fatty acid profile of BSF maggot cultived using animal and plant-based media. The study was conducted through experimental stages and laboratory analysis. The experimental stage was carried out through BSF maggot cultivation using two media treatments, namely animal and plant-based media. The laboratory analysis stage began with the preparation of maggot samples to become mash. Next, a fatty acid profile analysis was conducted at PT. Saraswanti Indo Genetech Surabaya using Gas Chromatography-Mass Spectrometry (GC-MS) to determine the type of fatty acids based on differences in volatility and molecular mass. The GC-MS results will provide quantitative data on the type and proportion of fatty acids continued in maggots. The parameters observed were water content, crude fat, and the fatty acid profile of maggots. The collected data were tabulated and discussed descriptively. Based on the results of laboratory analysis, it was found that maggots cultivated using animal media contained and average water content of 61.64% and crude fat of 55.48% (DM basis). Maggots cultivated using animal-source media contained higher unsaturated fatty acids than plant-source media. The highest laurate content was found in maggots cultivated using plant media (13.55%) compared to animal media (4.27%). The conclusion of this study is that the fatty acid profile is influenced by the growth media used, animal media will produce maggots with higher unsaturated fatty acids plant media will produce maggots with higher saturated fatty acids, especially lauric acid